Outcome of localised blastemal-type Wilms tumour patients treated according to intensified treatment in the SIOP WT 2001 protocol, a report of the SIOP Renal Tumour Study Group (SIOP-RTSG). Issue 4 (March 2015) - van den Heuvel-Eibrink, M.M.; van Tinteren, H.; Bergeron, C.; Coulomb-L'Hermine, A.; de Camargo, B.; Leuschner, I.; Sandstedt, B.; Acha, T.; Godzinski, J.; Oldenburger, F.; Gooskens, S.L.; de Kraker, J.; et al.
Abstract Blastemal-type Wilms tumour (BT-WT) has been identified as a high risk histological subgroup in WT assessed after pre-nephrectomy chemotherapy in trials of the International Society of Paediatric Oncology (SIOP) Renal Tumour Study Group. Therefore, in SIOPWT2001, post-operative chemotherapy for BT-WT was intensified aiming to improve survival. Survival analysis of all unilateral BT-WT patients (SIOPWT2001) (n = 238), was compared with historical BT-WT controls (SIOP93-01) (n = 113). 351/4061 (8.6%) unilateral non-metastatic BT-WT patients (SIOP93-01/SIOPWT2001) were studied. Median age at diagnosis was 43 months (Inter Quartile Range (IQR) 24–68 months), stages: I (n = 140, 40%), II (n = 106, 30%), III (n = 105, 30%). BT-WTs were higher staged, showed greater volume decrease after pre-operative chemotherapy and were diagnosed at an older median age compared to other WT patients. Patient characteristics did not differ substantially between SIOP93-01 and SIOPWT2001. Univariate analysis showed a 5-year event-free survival (EFS) of 80% (95% confidence interval (CI): 75–86%) (SIOPWT2001) compared to 67% in SIOP93-01 (95% CI: 59–76%; p = 0.006) and overall survival (OS) of 88% (95% CI: 83–93%) (SIOPWT2001) compared to 84% (95% CI: 77–91%; p = 0.4) in SIOP93-01. 95% of relapses were distant metastases (SIOP93-01/SIOPWT2001). Treatment protocol, age at diagnosis, tumour stage (III versus I/II) and volume (at surgery), were prognostic variables for EFS (uni- and multivariate Cox regression analysis). Independent prognosticators for OS were age at diagnosis, tumour stage and volume (at surgery). The most significant survival benefit of intensified treatment, was observed in Stage I (EFS 96% in SIOPWT2001 (OS 100%), 71% in SIOP93-01 (OS 90%)). BT-WT derived benefits from more intensive chemotherapy as reflected by a reduction in relapse risk. However, the benefit of the more intensive chemotherapy to improve OS was only observed in stage I BT-WTs, by adding doxorubicin.